Practical Android 4 games development - DiMarzio, J. F. (Apress, 2011)
Practical Android 4 Games Development continues your journey to becoming a hands-on Android game apps developer. This title guides you through the process of designing and developing game apps that work on both smartphones and tablets, thanks to the new Android SDK 4.0 which merges the User Interface and Experience APIs and more. The author, J.F. DiMarzio, has written eight books, including Android: A Programmer's Guide—the first Android book approved by Google—recently updated and translated for sale in Japan. He has an easy-to-read, concise, and logical writing style that is well suited for teaching complex technologies like the Java-based Android. From 2D-based casual games to 3D OpenGL-based first-person shooters, you find that learning how to create games on the fastest growing mobile platform has never been easier. Create 2D and 3D games for Android 4.0 phones and tablets such and the Motorola Xoom. Build your own reusable “black box” for game development. Easy-to-follow examples make creating the sample games a hands-on experience.